Efficient Radiative Enhancement in Perovskite Light‐Emitting Devices through Involving a Novel Sandwich Localized Surface Plasmon Structure. Issue 4 (10th March 2022) - Shao, He; Wu, Xiufeng; Zhou, Donglei; Chen, Wenda; Li, Lifang; Xu, Wen; Xu, Lin; Dong, Biao; Bai, Xue; Song, Hongwei
Abstract: In recent years, CsPbX3 (X = Cl, Br, I) perovskite quantum dots (QDs) have been considered as the most promising materials for light‐emitting diodes (LEDs). However, the advances of CsPbX3 quantum dot‐based light emitting diodes (QLEDs) still lagged behind inorganic III–V LEDs and other organic LEDs. Herein, a strategy to improve the performances of perovskite QLEDs is reported by utilizing the localized surface plasmon resonance (LSPR) effects of Au nanospheres (NSs). It is accomplished by introducing a Au NS layer into the electron transport layer of Ca 2+ ‐CsPbBr3 QLEDs, where the diameter and spacing of Au NSs and the interaction distance between the Ca 2+ ‐CsPbBr3 QD and Au NS layers are modulated, according to the theoretical simulation of Finite‐difference time‐domain. As a result, the photoluminescence quantum yield of Ca 2+ ‐CsPbBr3 QD layer is improved from 31.5% to 73.3%. Finally, the luminance of Ca 2+ ‐CsPbBr3 QLEDs is improved from 16824 to 63931 cd m –2 and external quantum efficiency (EQE) is improved from 4.2% to 10.5%. The radiative transition rate can be remarkably modulated from 0.7 × 10 7 to 6.6 × 10 7 s –1 . The enhancement in luminance and EQE are the best values in the LSPR modified perovskite QLEDs and the strategy offered in this work fits with other LEDs and optoelectrical devices. Abstract : The performance of Ca 2+ ‐CsPbBr3 quantum dot‐based light emitting diodes (QLEDs) is improved by utilizing the localized surface plasmon resonance effects of a Au nanospheres (NSs) layer. Benefiting from the precise modulation of the distance between the quantum dot (QD) layer and the Au NS layer, the diameter, and spacing of Au NSs, the external quantum efficiency and luminance of the device are improved 2.5‐fold and 3.8‐fold, respectively.